Cultural Transformation and Social Interaction in Indigenous Communities: The Impact of Digital Technology - Polnaya, Tiara; Murwani, Prapti; D. Pariela, Tonny (Universitas Pattimura, 2023)
This article explores cultural transformation and changes in social interaction within the indigenous community of Negeri Hatusua as a result of the introduction of digital technology, particularly smartphones and the internet. The main objective of this study is to uncover the shifts in values and norms within family structures as well as changes in social communication patterns in the digital era. The research adopts a qualitative approach through data collection techniques such as in-depth interviews, participatory observation, and documentation. Findings indicate that the presence of digital technology has shifted the community’s communication patterns from face-to-face interaction to indirect communication through digital devices. This shift affects relationships among family and community members, particularly in terms of information exchange and the practice of customary values. These findings affirm that digital technology plays a significant role in driving social and cultural change in indigenous societies, supporting previous studies and expanding the understanding of how local cultures adapt to global technological developments. The novelty of this research lies in its focus on indigenous communities, which have been relatively underrepresented in studies on digital technology. The study recommends strengthening digital literacy grounded in local wisdom to ensure that cultural transformations preserve indigenous identity and social cohesion. This research provides a valuable contribution to the development of the social sciences and humanities, particularly in understanding the impact of technology on traditional cultural values and social structures.